A combined low‐pressure hydrogen peroxide evaporation plus hydrogen plasma treatment method for sterilization – Part 1: Characterization of the condensation process and proof‐of‐concept. Issue 8 (10th February 2017) - Stapelmann, Katharina; Fiebrandt, Marcel; Raguse, Marina; Lackmann, Jan‐Wilm; Postema, Michiel; Moeller, Ralf; Awakowicz, Peter
Abstract : A combined hydrogen peroxide evaporation and hydrogen low‐pressure plasma treatment process for sterilization is introduced and investigated. The combination of hydrogen peroxide evaporation followed by hydrogen plasma treatment offers an advantage regarding sterilization in complex metal geometries or in sealed sterile bags, where plasma treatment alone faces challenges. Within this contribution, the droplet size and film homogeneity after condensation is investigated by optical diagnostics. Sterilization tests with common challenge organisms show the sterilization capabilities of the combined process in a process challenge device, mimicking the worst‐case‐scenario for plasma treatment in a small metal box. Furthermore, sterilization in sealed sterile bags clearly demonstrates the advantage of the combined process, showing full spore inactivation solely for the combined process. Abstract : Plasma sterilization is a promising alternative to conventional sterilization procedures. However, the efficiency of plasma sterilization processes is challenged by multilayered stacks of spores as plasma is a surface process. Furthermore, small, complex metal geometries pose a challenge due to shielding characteristics. A combined process of condensed hydrogen peroxide with subsequent hydrogen plasma treatment is introduced to overcome this challenges. The condensation process is investigated and a proof‐of‐concept is given by sterilization tests in a process challenge device and in sealed sterile bags.